Emergence and morphophysiology of Sunki mandarin and other citrus genotypes seedlings under saline stress - Brito, Marcos E. B.; Soares, Lauriane A. A.; Soares Filho, Walter S.; Fernandes, Pedro D.; Silva, Elaine C. B.; Sá, Francisco V. S.; Silva, Luderlândio A. (Spanish Journal of Agricultural Research, 2018)
The scarcity of good quality water is a limiting factor for irrigated agriculture, especially in arid and semiarid regions, where water sources generally contain high concentrations of ions. In such conditions, it is essential to cultivate genotypes with economic potential and tolerance to salinity. Considering the importance of citrus and the need to identify genetic materials that adapt to saline stress, this study evaluates the salinity tolerance of 10 genotypes with rootstock potential. For the irrigation water, five levels of electrical conductivity (ECw: 0.8, 1.6, 2.4, 3.2 and 4.0 dS/m at 25 °C) were used in a randomized block design with three replications, and seed germination and growth variables, as well as physiological plant parameters, were evaluated. The germination rate of the hybrid TSKC × CTARG – 019 was the best under salt conditions, as it was the genotype with the highest tolerance to salinity in the germination stage. Salinity reduced the growth of the citrus genotypes, with the possibility of using water with EC of up to 1.6 dS/m in the rootstock formation stage. Salt stress affected the photosynthetic rate of the genotypes ‘San Diego’ citrandarin and TSKC × CTSW – 018 by reducing the stomatal conductance, restricting the diffusion of CO2 into the substomatal camera. The genotypes TSKC × CTARG – 019, TSKC × CTTR – 012 and TSKC × TRBK – 007 have the greatest potential for growth and photosynthetic apparatus efficiency when subjected to salinity.